THU0571 Proteomic identification of systemic-onset juvenile idiopathic arthritis phenotypic biomarkers. (12th June 2018) - Gohar, F.; McArdle, A.; Jones, M.; Callan, N.; Hernandez, B.; Miranda-Garcia, M.; Lavric, M.; Kessel, C.; Holzinger, D.; FitzGerald, O.; Pennington, S.R.; Foell, D.
Abstract : Background: Systemic juvenile idiopathic arthritis (SJIA) is a childhood rheumatic auto-inflammatory disorder of largely unknown pathogenesis. The presence of fever, rash and arthritis support a diagnosis of SJIA, though early in disease arthritis may be minimal, complicating the exclusion of alternative diagnoses such as infection. Furthermore, two clinical phenotypes of SJIA can be identified, a chronic articular-dominant (ART_SJIA) and a classical auto-inflammatory phenotype (AID_SJIA). Objectives: To identify novel serum protein biomarkers that may discriminate ART_SJIA from AID_SJIA and distinguish AID_SJIA from infection. Methods: Patients with active SJIA (joint activity plus or minus fever and elevated laboratory inflammation markers) were sub-grouped into the two clinical phenotypes (ART_SJIA and AID_SJIA). Serum from patients with SJIA or confirmed infection was analysed for the standard laboratory markers: C-reactive protein (CRP), white cell count (WCC) and erythrocyte sedimentation rate (ESR). A "discovery cohort" (n=10 per group) of patient serum samples was subjected to unbiased label-free proteomics using liquid chromatography mass spectrometry (LC-MS/MS) and in a separate "verification cohort" (AID_SJIA, n=48; ART_SJIA, n=29; infection, n=32) candidate biomarkers were measured by multiple reaction monitoring MS (MRM-MS; Agilent 6490 and 6495) and microsphere bead-based immunoassay (Luminex). Serum concentrations of S100A12 and MRP8/14 were also measured in all samples using enzyme linked immunoabsorbant assays (ELISAs). Results: The routine laboratory markers CRP, WCC, ESR, as well as ELISA-measured S100A12 and MRP8/14 serum concentrations were highest in AID_SJIA, followed by infection and were lowest in patients with ART_SJIA. Proteins identified and quantified by LC-MS/MS could differentiate patients with ART_SJIA from those with AID_SJIA (area under the curve, AUC: 0.97). The discrimination between AID_SJIA and infection performed less well, AUC: 0.58. Targeted MRM measurement of novel protein candidate biomarkers verified the discovery cohort data. A combined biomarker panel consisting of MRM, ELISA and Luminex analysis which was evaluated using a Random forest model, indicated the correct overall identification of the clinical groups to be as follows: ART_SJIA: 24/29 (83%), AID_SJIA: 37/45 (82%) and infection: 20/32 (63%). Conclusions: Significant differences in the serum protein signature between two phenotypes of SJIA suggest that different immunological processes may underlie these phenotypes. Serum protein profiles also distinguished patients with SJIA and infection. Distinguishing these two groups remains an important goal of research and therefore this study could help inform future prospective studies. Disclosure of Interest: None declared